2013
DOI: 10.1254/jphs.13170sc
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Serotonin Receptors Co-mediate Non-photic Signals to the Circadian Clock

Abstract: Abstract. Several lines of evidence indicate that serotonin type 7 (5-HT 7 ) receptors play a critical role for non-photic resetting of the mammalian circadian clock; however, the contributions of other types of 5-HT receptors to non-photic entrainment are not yet clarified. The present study demonstrates that MKC-242, a selective 5-HT 1A receptor agonist, can evoke a non-photic-like phase-response in hamsters in vivo. This phase-shifting response to MKC-242 was antagonized not only by the selective 5-HT 1A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…This finding was later confirmed with the more selective 5-HT7 receptor antagonist SB-269970 (Sprouse et al, 2004 ). In vivo studies later reported the translational aspects of this cell model by demonstrating that phase advances in wheel running activity induced by 8-OH-DPAT were blocked following the administration of the 5-HT7 receptor antagonist DR-4004 in hamsters and absent in the 5-HT7 receptor knockout (KO) mouse (Ying and Rusak, 1997 ; Ehlen et al, 2001 ; Horikawa and Shibata, 2004 ; Gardani and Biello, 2008 ; Horikawa et al, 2013 ). In addition to its effects on the non-photic regulation of circadian rhythms, there is evidence that the 5-HT7 receptor may also influence photic regulation of circadian rhythms either by altering the sensitivity to light or modulating the release of serotonin (Ying and Rusak, 1997 ; Smith et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…This finding was later confirmed with the more selective 5-HT7 receptor antagonist SB-269970 (Sprouse et al, 2004 ). In vivo studies later reported the translational aspects of this cell model by demonstrating that phase advances in wheel running activity induced by 8-OH-DPAT were blocked following the administration of the 5-HT7 receptor antagonist DR-4004 in hamsters and absent in the 5-HT7 receptor knockout (KO) mouse (Ying and Rusak, 1997 ; Ehlen et al, 2001 ; Horikawa and Shibata, 2004 ; Gardani and Biello, 2008 ; Horikawa et al, 2013 ). In addition to its effects on the non-photic regulation of circadian rhythms, there is evidence that the 5-HT7 receptor may also influence photic regulation of circadian rhythms either by altering the sensitivity to light or modulating the release of serotonin (Ying and Rusak, 1997 ; Smith et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%